Acute Stroke - Morotti, Andrea; Poli, Loris; Costa, Paolo (Seminars in Neurology, 2019)
Stroke remains one of the leading determinants of death and severe disability worldwide. It is a medical emergency with a narrow window for recognition and administration of outcome-modifying treatment in the emergency department. Ischemic stroke accounts for the majority of cerebrovascular events and revascularization therapies such as intravenous thrombolysis and endovascular thrombectomy are the mainstays of treatment in carefully selected patients. Intracerebral hemorrhage is less common but remains the deadliest type of stroke. Blood pressure reduction and hemostatic treatment in case of coagulopathy are the cornerstones of acute intracerebral hemorrhage treatment. Admission to dedicated stroke units is associated with improved outcome in patients suffering from acute stroke.
Keywords: stroke; ischemia; intracerebral hemorrhage; diagnosis; treatment